An overview of studies on early life history of fish in Vietnam - Hau, Tran Duc; Tran, Thanh Trung; Thuy, Ta Thi; Izumi, Kinoshita (Academia Journal of Biology, 2019)
Early stages from fertilized eggs to juveniles are important in the existence and development cycles of fish. At these stages, fish are still not fully developed, and are thus easily affected by environmental factors. Vietnam has a rich fish diversity, with ca. 3000 species, and fishery resources play significantly roles not only in the daily lives of local residents but also in national economic development. Ichthyological studies in Vietnam have focused mainly on matured fish while early life history has so far been less researched. This paper presents an overview of studies in Vietnam related to early stages of fish and provides an orientation for this field in future.